A voice and nothing more - Dolar, Mladen (Short circuits., 2006)
The voice was not a major philosophical topic until the 1960s, when Derrida and Lacan separately proposed it as a central theoretical concern. Here, Dolar goes beyond Derrida's idea of "phonocentrism" and revives and develops Lacan's claim that the voice is one of the paramount embodiments of the psychoanalytic object. He proposes that, apart from the uses of the voice as a vehicle of meaning and as a source of aesthetic admiration, there is a third level of understanding: the voice as an object that can be seen as the lever of thought. He investigates the object voice on a number of different levels--linguistics, metaphysics, ethics (the voice of conscience), the paradoxical relation between the voice and the body, the politics of the voice--and finally scrutinizes the uses of the voice in Freud and Kafka. With this foundational work, Dolar gives us a philosophically grounded theory of the voice as a Lacanian object-cause.--From publisher description.